Debt policy score and performance score among energy companies: Empirical evidence - Aljaaidi, Khaled; Alwadani, Neef (Asian Economic and Financial Review, 2025)
The objective of this study is to examine the association between debt policy and financial performance among Saudi Arabian energy companies. The final sample consists of 18 firm-year observations listed on the Saudi Stock Exchange (Tadawul) from 2021 to 2023. This study used a quantitative-based method, and the data were hand-collected from the annual reports of the sample companies. The result of the Pooled Least Square regression (OLS) reveals a statistically significant positive relationship between debts and financial performance. This indicates that the higher the level of debt structure among energy companies in Saudi Arabia, the higher the performance they achieve. The energy companies use the debts as an external financing source to effectively and efficiently finance their investing activities. This finding backs up the trade-off and agency cost theories, which say that good debt management improves company performance by making the best use of capital structure. This study has implications for corporate finance decision-making in the energy sector, emphasizing the importance of balancing debt to foster financial growth. It contributes to the corporate finance literature by providing empirical evidence specific to the Saudi energy sector, highlighting both the benefits and complexities of debt policies. In specific, the results have significant implications for managers, investors, and policymakers regarding capital structure decisions and financial performance optimization.